Prevalence of Banana Xanthomonas Wilt in Nithi, Tharaka-Nithi County in Kenya - Onyambu, Mogaka M.; Moses, Muraya M.; Benson, Onyango O.; Peterson, Ong’au, M.; Fredrick, Ogolla O. (Machakos University Press, 2021)
Banana (Musa spp.) is a nutrient rich crop that is grown in small and large scale across the globe. It is rich in carbohydrates, vitamins and minerals thus, may serve as the source of nutrition in low resourced regions such as Tharaka Nithi County, Kenya. However, banana production in many areas is faced with biotic constraints such as banana Xanthomonas wilt (BXW) disease caused by Xanthomonas campestris p.v musacearum. The pathogen attacks photosynthetic leaves and young fruits, reducing palatability and marketability. There is currently scanty information on prevalence of BXW in Nithi region of Tharaka Nithi County. Additionally, it remains unclear whether farmers in the region are knowledgeable on occurrence of BXW disease, symptoms and management practices. The prevalence of BXW was assessed through survey method in five villages (Kiang’ondu, Marima, Mitheru, Kibumbu and Giampampo) in Nithi. Percentage BXW prevalence in the studied villages was not significantly different (p>0.05). However, slightly higher BXW prevalence value of 21.14% was recorded at Giampampo village and was lower at Mitheru 11.24%. There was significant relationship (X2 (8, N = 46) = 19.93, p= 0.0034) between banana variety grown and occurrence of banana diseases. There was significant relationship (X2 (8, N = 46) = 31.165, p = 0.0053) between banana variety grown and susceptibility to diseases. The relationship between years of growing banana in the same farm and occurrence of banana diseases was significant (X2 (6, N= 46) = 8.761, p <0.0001. The relationship between occurrence of banana diseases and season of the year was significant (X2 (8, N= 46) = 32.4591, p <0.0001). The relationship between occurrence of banana diseases and management option in Nithi was significant (X2 (4, N= 46) = 6.9758, p= 0.0025). Majority of the farmers (92%) were unaware of existence of BXW in the region. Farmers expressed lack of knowledge on methods of managing BXW diseases in their banana farms with majority not being able to identify common diseases of banana. Based on these observations, there is need to educate farmers on best banana farming practices, disease identification and management.
Keywords: Banana; Xanthomonas-wilt; Tharaka-Nithi; Kenya